On bistochastic Kadison-Schwarz operators onM2(ℂ) - Mukhamedov, Farrukh; Abduganiev, Abduaziz (Institute of Physics Publishing (UK), 2013)
In this paper we describe bistochastic Kadison-Schawrz operators acting on M2(C). Such a description allows us to nd positive, but not Kadison-Schwarz operators. Moreover, by means of that characterization we are able to construct Kadison-Schawrz operators, which are not completely positive.